Mediation: education for human rights and skills in the culture of dialogue - Beltrán, Helena Pérez (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Mediation is proving to be an effective way to manage conflicts in a constructive way. But mediation not only helps to solve specific problems, because its potential encompasses aspects of greater complexity. Thus, mediation helps us to know ourselves better, to better understand others, and to use what we have learned to better manage future conflict situations. In a society where there is no culture of agreement and where there is no education in the field of emotions, mediation becomes an adequate and effective tool to resolve conflicts in a peaceful and constructive manner. On the other hand, mediation allows the parties to take responsibility for the resolution of their own conflict, to be active agents in the process. The greater the citizens’ participation in the different decision making processes, the more democratic a society will be. That is why, in the restoration of social peace, citizenship should play a role as an active agent, and mediation is a suitable instrument for this purpose because the individuals in conflict find the way to solve it without third party impositions.